Family Physicians’ Quality Interventions and Performance Improvement Through the ABFM Diabetes Performance in Practice Module - Peterson, Lars E. (American Academy of Family Physicians, 2014)
PURPOSE: Practice performance assessment is the fourth requirement of Maintenance of Certification for Family Physicians (MC-FP). American Board of Family Medicine (ABFM) diplomates have many options for completing Part 4 requirements, including Web-based Performance in Practice Modules (PPMs) developed by the ABFM. Our objective was to describe the actions and outcomes of family physicians who completed the ABFM diabetes PPM. METHODS: We undertook a descriptive study of all diabetes PPMs completed by physicians in the 50 United States and Washington, DC, from 2005 to October 2012. Successful completion required quality measure abstraction from 10 patient charts before and after a plan-do-study-act cycle improvement effort. We used descriptive statistics to assess physician demographics and quality outcomes. RESULTS: Family physicians completed 7,924 diabetes qualitative improvement modules. Their mean age was 48.2 years, they had practiced a mean of 13.8 years, and three-fourths lived in urban areas (76.9%). Nearly one-half selected diabetic foot examination or eye examination as their quality improvement measure. Performance on all quality measures improved. Significant improvement was seen in rates of hemoglobin A(1c) control (<7.0%; 57.4% to 61.3%), blood pressure control (<130/90 mm Hg; 53.3% to 56.3%), foot examinations (68.0% to 85.8%); and retina examinations (55.5% to 71.1%). The most common interventions were standing orders (51.6%) and patient education (37.1%). CONCLUSIONS: Family physicians participating in MC-FP implemented improvement projects and showed quality improvements in caring for patients with diabetes. Emphasis on quality of care by payers will increasingly require physicians to embrace quality measurement and improvement.